(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Motivation is a very significant and effective element in the realm of learning language. Thus, the language teachers should discover, realize and pay attention to the personality of their learners. However, they should be aware of motivation, its high importance, and its types.